Changes of a Landfill Leachate Toxicity as a Result of Treatment With Phragmites australis and Ceratophyllum demersum–A Case Study - Szymańska-Pulikowska, Agata; Wdowczyk, Aleksandra (Frontiers in Environmental Science, 2021)
Most phytoremediation studies are limited to several of the most common plants and in most cases these studies are performed to a very limited extent. There are also few publications on the assessment of the effectiveness of the removal of pollutants, performed simultaneously with various plants and using physicochemical analyses as well as toxicity tests. Therefore, the conducted studies focused on assessing the removal of pollutants from leachate by physicochemical analyses and toxicity tests. The leachate was collected from four municipal waste landfills of different ages (2 non-operational facilities and 2 active). The studies were conducted for two biological systems: using emergent macrophytes (Phragmites australis) and submergent macrophytes (Ceratophyllum demersum L.). It has been observed that efficiency of biological treatment of leachates with Phragmites australis and Ceratophyllum demersum shows significant differences at lower concentrations of solutions. Even after the treatment with Phragmites australis and Ceratophyllum demersum, the analyzed leachate samples produced a toxic effect on the test organisms. A reduction or no toxicity of the leachate after the biological treatment was observed only in some cases. The observed effects of the biological leachate treatment were not conclusive. Particular attention should be paid to the persistent toxicity, which can pose a real threat to the environment when discharging leachates after treatment.